2020
DOI: 10.4314/ijbcs.v14i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arbuscular mycorrhizal fungus (<i>Rhizophagus irregularis</i>) on disease symptoms caused by the ascomycete fungus (<i>Mycosphaerella fijiensis M.</i>) in Black Sigatoka-resistant banana plantain

Abstract: Banana (Musa spp.) is grown throughout the tropical and subtropical areas. The Black Sigatoka, however, represents a major threat to world production. This study evaluates the effect of the arbuscular mycorrhizal fungus (AMF) Rhizophagus irregularis MUCL 41833 on four plantain cultivars with different resistance against Mycosphaerella fijiensis. The mycorrhized banana plantlets of four cultivars were grown under greenhouse and the effect of AMF on micropropagated banana plantlets was evaluated. After 35 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…After 35 days of growth, it was observed that AM fungi inoculated CRBP39 and F568 showed more resistance than Batard and C292 cultivars toward M. fijiensis. The overall study signifies that AMF inoculation resists the development of host plant infectious symptoms by M. fijiensis at an early age of infection (Anda et al 2020). Symbiotic association of AM fungi R. intraradices, with alfalfa (Medicago sativa), decreases the incidence of leaf spot disease caused by the fungus Phoma medicaginis by 39.48% and also reduces its disease index by 56.18% .…”
Section: Other Fungal Foliar Diseasesmentioning
confidence: 79%
“…After 35 days of growth, it was observed that AM fungi inoculated CRBP39 and F568 showed more resistance than Batard and C292 cultivars toward M. fijiensis. The overall study signifies that AMF inoculation resists the development of host plant infectious symptoms by M. fijiensis at an early age of infection (Anda et al 2020). Symbiotic association of AM fungi R. intraradices, with alfalfa (Medicago sativa), decreases the incidence of leaf spot disease caused by the fungus Phoma medicaginis by 39.48% and also reduces its disease index by 56.18% .…”
Section: Other Fungal Foliar Diseasesmentioning
confidence: 79%
“…Biological control measures such as arbuscular mycorrhizal fungi (AMF) have shown an increase in plant resistance against diseases (Anda et al, 2020;Dey and Ghosh, 2022). AMF are obligate root symbionts that form associations with about 80% of terrestrial plant species, including beans, maize, tomato, and potato.…”
Section: Original Research Articlementioning
confidence: 99%